Trash Talk Dan Transformasi Diri: Refleksi Filsafat Komunikasi Terhadap Budaya Verbal Dalam Game Online - Devin Sachio Beiskom; Nina Yuliana (Program Studi Ilmu Komunikasi, FISIP Unismuh Makassar, 2026)
Trash talk has become an integral element of communication among online gamers and is often perceived as a spontaneous expression triggered by competitive tension. However, its influence extends far beyond momentary emotional reactions, shaping how players communicate, construct their identities, and negotiate social meaning within virtual and real-life interactions. This study aims to examine the verbal culture of trash talk through the lens of communication philosophy by exploring its ontological, epistemological, and axiological dimensions, while also integrating perspectives from symbolic interactionism, speech act theory, and constructivism. Using a literature review method, this article analyzes various studies that address verbal behavior in online games, digital communication ethics, and the linguistic impact of gaming on players’ character and social interactions. The findings indicate that trash talk is not merely an emotional outburst, but a symbolic communicative practice that emerges through repeated interactions within gamer communities. The use of harsh language and specific expressions contributes to the formation of shared meanings and group identity, functioning as markers of social positioning in digital competition. Conversely, this phenomenon reveals shifts in values and ethical challenges, as the normalization of verbal aggression risks influencing players’ attitudes, emotional responses, and interpersonal behavior. This study highlights the importance of a philosophical perspective to understand trash talk more comprehensively, particularly regarding how it constructs meaning, shapes social relations, and contributes to players’ self-transformation within the increasingly dominant culture of online gaming.